The impact of an intervention to increase follow-up blood cultures for patients with Staphylococcus aureus bacteriuria - Jared Olson; Vincent Anella; Brandon J. Webb; Andrew T. Pavia; Emily A. Thorell; Adam L. Hersh; Dustin Waters (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract